2012
DOI: 10.1038/modpathol.2012.35
|View full text |Cite|
|
Sign up to set email alerts
|

Histological and genetic evidence for a variant of superficial spreading melanoma composed predominantly of large nests

Abstract: Cutaneous melanomas are characterized by a range of histological appearances, and several morphological variants have been described. In this study, we report a variant of superficial spreading melanoma that is characterized by large, irregular junctional melanocytic nests. The junctional nests varied in shape and size, showed focal tendency to confluence, and were often surrounded by a cuff of epidermal keratinocytes. The melanocytes comprising the nests showed variable cytological atypia. In most of the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 16 publications
(27 reference statements)
2
32
0
1
Order By: Relevance
“…Eighteen cases (4.04%) presented almost exclusively by large irregular nests, matching the description of the variant reported by Kutzner et al 5 Among these, we identified a patient who developed recurrence 61 months after the diagnosis. Five patients between the other 427 cases presented recurrence and three developed regional metastasis.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Eighteen cases (4.04%) presented almost exclusively by large irregular nests, matching the description of the variant reported by Kutzner et al 5 Among these, we identified a patient who developed recurrence 61 months after the diagnosis. Five patients between the other 427 cases presented recurrence and three developed regional metastasis.…”
supporting
confidence: 57%
“…The authors emphasized that the 11 cases were initially diagnosed as MIS and, after several serial sections, atypical melanocytes infiltrating the dermis were identified in five cases. 5 We identified 445 cases of primary MIS in two hospitals of Rio de Janeiro state, between 1998 and 2010, reviewing the slides to classify them as "large nests in situ melanomas" and other histopathological aspects. All cases were treated surgically with, at least, 5 mm free margins.…”
mentioning
confidence: 99%
“…Можно также отметить, что ряд меланом с характерными молекулярными изменениями характеризуется патомор-фологическими особенностями. Так, при поверхностно распространяющихся меланомах, мутантных по CDKN2A, наблюдается педжетоидный вариант и высокий уровень содержания пигмента [11].…”
Section: архив патологии 4 2015unclassified
“…1 The recognition of this particular pattern without a pagetoid element has been delayed as the histopathology masquerades as an unusual nevus. The clinical features, dermoscopy, the distinctive histopathology and now the application of comparative genomic hybridization, all help to identify this as a melanoma variant.…”
Section: Nested Melanomamentioning
confidence: 99%